CEE Trade in Services: Value-Added Versus Gross Terms Approaches. Issue 4 (4th July 2018) - Kordalska, Aleksandra; Olczyk, Magdalena
Abstract : This article assesses the impact of the determinants of service exports in both value-added terms and gross terms for seven Central Eastern European economies in 1995–2011. The results confirm the importance of increasing labor productivity and highly skilled and medium-skilled workers in the growth of trade in services. Exports of services are also supported by linkages between domestic services, especially business services, and the manufacturing sector. The results show that the impacts of the determinants are fairly similar when exports are measured in value-added or gross terms; however, the strength of the impact differs across the countries analyzed.